2017
DOI: 10.1111/eufm.12136
|View full text |Cite
|
Sign up to set email alerts
|

Consistent valuation of project finance and LBOs using the flows‐to‐equity method

Abstract: The flows‐to‐equity method is used to value transactions where debt amortizes according to a fixed schedule, requiring a formula that links the changing leverage with a time‐varying equity discount rate. We show that extant formulas yield incorrect valuations because they are inconsistent with the basic assumptions of this method. The error from using the wrong formula can be large, especially at currently low interest rates. We derive a formula that captures the effects of a fixed debt plan, potentially expen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The flows to equity method can be reconciled with standard valuation methods. Doing so reveals several interesting issues that are not usually addressed explicitly when standard methods are used (Cooper and Nyborg, 2018). Consider, for example, the treatment of the debt spread.…”
Section: Reconciling the Flows To Equity Methods With 'Standard' Methodsmentioning
confidence: 99%
“…The flows to equity method can be reconciled with standard valuation methods. Doing so reveals several interesting issues that are not usually addressed explicitly when standard methods are used (Cooper and Nyborg, 2018). Consider, for example, the treatment of the debt spread.…”
Section: Reconciling the Flows To Equity Methods With 'Standard' Methodsmentioning
confidence: 99%
“…As a result, the success of the projects will be difficult. Similarly, Cooper and Nyborg [22] identified that the fact that companies are exposed to too much liquidity risk increases the probability that the project will fail. In addition to these studies, Montgomery et al [23], Sainati et al [24] and Rode et al [25] focused on this issue for different countries, such as UK, Turkey, Indonesia, Malaysia and Brazil.…”
Section: Literature Review On the Financing Of Large-scaled Projectsmentioning
confidence: 99%
“…However, the authors do not take into account either debt-equity conversion or sustainability issues. In this line, studies raised and developed new investment valuation models applied to infrastructure systems (Cooper and Nyborg, 2018;DiMuro et al, 2014;Hajji et al, 2017;Ho and Liu, 2002;Huang and Pi, 2014;Jackowicz et al, 2017;Jeong et al, 2016;Kashani et al, 2015;Kim et al, 2013;Lu et al, 2016;Pantelias and Zhang, 2010;Wibowo, 2006;Yan et al, 2017) and significant works on sustainable infrastructure financing. For example, Büyüközkan and Karabulut (2018) provided a structured overview of analytical assessment methods into conceptual sustainability frameworks; Lee and Zhong (2015) developed a financing instrument that securitises future income in the form of a hybrid bond for renewable energy projects; Shen et al (2016) examined the impacts of the contribution distribution between public and private sectors on project sustainability performance; Shen et al (2002) developed an alternative quantitative model for assessing the feasibility that a construction project gets involved in contributing to sustainable development; Quesnel et al (2017) developed a conceptual financing model for the water sector based on the electricity sector; Quesnel and Ajami (2018) examined advanced water financing through public benefit funds; and Shan et al (2017) analysed innovative models and mechanisms for sustainable construction finance.…”
Section: Ecam 265mentioning
confidence: 99%
“…From the sponsor's point of view, the selection of the discount rate is one of the crucial aspects of economic engineering analysis given that it represents the opportunity cost of money to the party considering some investment (Zhang, 2005). For this issue, the capital asset pricing model (CAPM), which is widely used both in corporate valuation (Damodaran, 2012;McKinsey & Company et al, 2015) and valuation techniques for infrastructure investment decisions (Cheah and Liu, 2006;Cooper and Nyborg, 2018;Dong et al, 2011;Garvin and Cheah, 2004;Menassa, 2011;Brandao and Saraiva, 2008;Wibowo, 2006;Ye and Tiong, 2000), is used for estimating the sponsor's discounted rate (k e ).…”
Section: Financial Captured Value By Lenders Theorymentioning
confidence: 99%
See 1 more Smart Citation